Quality, Satisfaction and Customers’ Future Intention: The Case of Hotels’ Fitness Centers in Cyprus - Zopiatis, Anastasios; Theocharous, Antonis L.; Constanti, Panayiotis; Tjiapouras, Lambros (My University, 2017)
In an era of fierce competition, financial hardship, and volatile customer expectations the hospitality industry is seeking out new revenue centers that can both enrich the customer experience, and contribute to financial success. Capturing the attention of the industry, fitness centers have become a fundamental component of the contemporary hospitality experience with numerous strategic, operational and tactical implications. Responding to the need for further empirical investigation, the study, by adopting a quantitative methodology, holistically investigates quality, satisfaction, and behavioral intention in fitness centers currently operating in upscale hospitality establishments in Cyprus. Findings suggest that satisfaction with the provision of fitness services in hotels is primarily associated with the dimensions of employee behavior and workout facilities. Moreover, workout facilities was the only quality dimension which was significantly associated with the respondents’ intention to renew their membership, whereas a strong relationship between satisfaction and future intention was substantiated.
Keywords: Behavioral intention; Fitness centers; Quality; Satisfaction; Structural Equation Modeling (SEM)